2021
DOI: 10.1097/md.0000000000024758
|View full text |Cite
|
Sign up to set email alerts
|

The clinical efficacy of external application of mirabilite and rhubarb combined with intrathoracic chemotherapy in treating malignant pleural effusion

Abstract: Background: Malignant pleural effusion (MPE) is one of the commonest causes of an exudative pleural effusion. Breathlessness, dyspnea and other symptoms often seriously distress and affect the quality of life. The external application of mirabilite and rhubarb (EAMR) combined with intrathoracic infusion of cisplatin, as an alternative treatment for MPE, is popular in China. The study aims to assess its effectiveness and safety combined with intrathoracic chemotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…In combination with the conventional cisplatin treatment of patients with malignant pleural effusion, Zhang et al (2021) employed the external application of mirabilite plus R. palmatum, the results showed the total effective rate of patients in the treatment group (66.67%) was significantly higher than that in the control group (54.76%). Zhang (2019) treated 90 patients with edema after hemorrhoid surgery with the ratio of R. palmatum and mirabilite mixed with 1:3 band and found that the effective rate and recovery rate were 93.09% and 27.58%, respectively.…”
Section: Clinical Applications Of Mirabilitementioning
confidence: 99%
“…In combination with the conventional cisplatin treatment of patients with malignant pleural effusion, Zhang et al (2021) employed the external application of mirabilite plus R. palmatum, the results showed the total effective rate of patients in the treatment group (66.67%) was significantly higher than that in the control group (54.76%). Zhang (2019) treated 90 patients with edema after hemorrhoid surgery with the ratio of R. palmatum and mirabilite mixed with 1:3 band and found that the effective rate and recovery rate were 93.09% and 27.58%, respectively.…”
Section: Clinical Applications Of Mirabilitementioning
confidence: 99%
“…Quyu Xiaozhong recipe (QYXZR) consists of rhubarb powder (30 g) and mirabilite (120 g), and they were confirmed to have broad anti-inflammatory and antioxidant properties. Modern pharmacological studies have shown that external applications of rhubarb and mirabilite is effective in relieving the symptoms of acute pancreatitis [7]. The above reports suggest that QYXZR has obvious anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 97%